Combination and sequential treatment in women with postmenopausal osteoporosis. (3rd March 2020) - Anastasilakis, Athanasios D.; Polyzos, Stergios A.; Yavropoulou, Maria P.; Makras, Polyzois
ABSTRACT: Introduction : Since postmenopausal osteoporosis is a chronic, potentially disabling condition requiring long-term treatment, the physician is expected to decide the optimal treatment strategy, e.g. how to use the available osteoanabolic and antiresorptive agents, sequentially or in combination, in the most effective and safe way, based on personalized patient care. Areas covered : Herein, the authors outline clinical data regarding the efficacy and safety of various sequential treatment strategies. More specifically, they compare the efficacy of osteoanabolic agents when they precede or follow antiresorptive treatment, as well as the efficacy of antiresorptives following other antiresorptives. Finally, the authors quote and discuss available evidence regarding the efficacy and safety of the co-administration of osteoanabolics and antiresorptives in comparison with monotherapies. Expert opinion : Initiation with an osteoanabolic agent followed by an antiresorptive seems to be the optimal treatment sequence, at least in patients with severe osteoporosis. Osteoanabolic treatment following antiresorptives seems to lead in more modest responses in bone mineral density (BMD) and bone turnover markers. Combination therapy with teriparatide and denosumab or zoledronate has achieved higher BMD gains compared to each agent alone; however, due to the high cost, combination therapy is rarely compensated. On the contrary, the combination of teriparatide with alendronate results in smaller BMD increases than TPTD monotherapy.